A-158 The Effect of Adverse Childhood Experiences on Attentional Bias. (28th August 2020) - R, Owens; S, Smith; S, Lindsey; C, Marker; B, Robinson
Abstract: Objective: This study aims to investigate the relationship between Adverse Childhood Experiences (ACEs, specifically household dysfunction) and attentional bias. Research has shown that ACEs can induce psychological stress and result in greater risk for neuropsychological difficulties among children who experience them (Raver and Blair., 2016). Therefore, we hypothesize that children with higher levels of ACE exposure will show higher levels of attentional bias overall. Data Selection: Data was obtained through the longitudinal Adolescent Brain Cognitive Development Study. The broader dataset was narrowed to include variables related to household dysfunction: Parent Family Environment Scale—Family Conflict Subscale Modified from PhenX and Parent Neighborhood Safety/Crime Modified from PhenX. Attentional bias was measured via the Youth Emotional Stroop Test. Data Synthesis: Data was analyzed using a Bivariate correlation between predictor variables and participant latency on incongruent items within the Youth Emotional Stroop Test. Neighborhood crime and response latency were significantly correlated at r(4838) = −.041, p < .001. Neighborhood crime and family conflict were significantly correlated at r(4838) = −.040, p < .001. Additionally, we used linear regression to examine the roles of neighborhood crime and family conflict as predictors of attentional bias (N = 4838). The two variables together significantly predicted attentional bias, F(2, 4835) = 4.50, p = .012, r2 .002. Conclusion: Although family conflict was not significantly related to attentional bias, our results support previous research and our hypothesis that higher levels of exposure to ACEs are significantly associated with an increase in attentional bias for environmentally threatening stimuli (Caldwell., Carter., and Minzenberg 2014).